(untitled) (Stamford Journal of Microbiology, 2020)
Hand hygiene is the most simple and effective way to prevent infection. Contaminated hand and related ornaments act as a vector of transmitting diseases. The main goal of this study was to find out whether personal accessories of different categories of working women are responsible for foodborne illness or contagious diseases. For this purpose, six categories of individuals were chosen, and five types of ornaments were taken from each individual. Total thirty swab samples were taken from the surface of bangles, nose pins, ear rings, finger rings and chains. Conventional culture techniques and biochemical tests were performed to determine the presence and identification of the pathogenic microorganisms. Total viable bacteria was present in all those samples but the presence of specific microorganisms were not found in all of those samples. Moderate growth of Staphylococcus spp. was found in finger rings and ear rings of the home makers and presence of Escherichia coli was detected in 16% of these samples as an indicator of fecal contamination. In the light of these results, it is essential to maintain proper hand hygiene and sanitation practice as some ornaments could be the significant source of pathogenic microorganisms. Food handlers and health care workers should abide by the rules and regulations of personal hygiene. Stamford Journal of Microbiology, Vol.10 (1) 2020: 5-8